Intergenerational displacement in Indonesia's oil palm plantation zone. Issue 6 (2nd November 2017) - Li, Tania Murray
Abstract : This contribution examines the intergenerational effects of oil palm expansion in Indonesia at two scales. First, I use a broad brush and selected examples from different parts of Indonesia to highlight the long-term, intergenerational dynamics of displacement from the land, and the linked problem of displacement from opportunities to find decent work. In the second part I draw on primary data from my research in a plantation zone in West Kalimantan to examine intergenerational dynamics in households and communities tucked around the borders of plantations, where access to residual pockets of land is the key to secure to secure and prosperous futures.